2D Materials: Synaptic Barristor Based on Phase‐Engineered 2D Heterostructures (Adv. Mater. 35/2018). Issue 35 (26th August 2018) - Huh, Woong; Jang, Seonghoon; Lee, Jae Yoon; Lee, Donghun; Lee, Donghun; Lee, Jung Min; Park, Hong‐Gyu; Kim, Jong Chan; Jeong, Hu Young; Wang, Gunuk; Lee, Chul‐Ho
Abstract : In article number 1801447, Gunuk Wang, Chul‐Ho Lee, and co‐workers report an artificial synaptic architecture by monolithically integrating a memristor and a barristor using phase‐engineered 2D heterostructures. This three‐terminal artificial synapse, termed as a "synaptic barristor", can implement fundamental synaptic functions with external gate controllability. Such unique capabilities enable the accelerated consolidation and conversion of synaptic plasticity, functionally analogous to the synapse with an additional neuromodulator in biological neural networks.